1998
DOI: 10.1128/iai.66.8.3892-3899.1998
|View full text |Cite
|
Sign up to set email alerts
|

Infection of the Laboratory Mouse with the Intracellular PathogenEhrlichia chaffeensis

Abstract: To determine the basis of susceptibility and resistance to human monocytic ehrlichiosis (HME), immunocompetent and immunocompromised mice were infected with Ehrlichia chaffeensis and bacterial loads were measured by PCR and by immunohistochemistry. Immunocompetent (C.B-17 and C57BL/6) mice cleared the bacteria within 10 days, but immunocompromised SCID and SCID/BEIGE mice developed persistent infection in the spleen, liver, peritoneal cavity, brain, lung, and bone marrow and became moribund within 24 days. Bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
38
0
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(40 citation statements)
references
References 23 publications
0
38
0
2
Order By: Relevance
“…5,34,36,41,43,[53][54][55] In contrast, immunocompetent mice are not generally susceptible to E. chaffeensis infection, 56 yet SCID mice rapidly die after infection associated with unrestricted bacterial growth, suggesting that intact immunologic mechanisms are protective rather than detrimental. 57 Another animal model that closely mimics HME uses the related Ixodes ovatus ehrlichia, and fatal infection in this system is associated with high serum TNFα, low serum IL-12, TNFαproducing CD8 cells, and low levels of IFNγ-producing CD4 cells. 47 Although the specific immunologic mechanisms have yet to be discerned, it is clear that there is an inter-relationship between the bacterial trigger and subsequent immunologically mediated tissue and organ injury.…”
Section: Pathology and Pathophysiologymentioning
confidence: 99%
“…5,34,36,41,43,[53][54][55] In contrast, immunocompetent mice are not generally susceptible to E. chaffeensis infection, 56 yet SCID mice rapidly die after infection associated with unrestricted bacterial growth, suggesting that intact immunologic mechanisms are protective rather than detrimental. 57 Another animal model that closely mimics HME uses the related Ixodes ovatus ehrlichia, and fatal infection in this system is associated with high serum TNFα, low serum IL-12, TNFαproducing CD8 cells, and low levels of IFNγ-producing CD4 cells. 47 Although the specific immunologic mechanisms have yet to be discerned, it is clear that there is an inter-relationship between the bacterial trigger and subsequent immunologically mediated tissue and organ injury.…”
Section: Pathology and Pathophysiologymentioning
confidence: 99%
“…Intracellular killing of E. chaffeensis requires CD4+ T cell-dependent cellular effector mechanisms, including NO production by IFN-γ-activated macrophages, and granulomatous inflammation. 4,5 The role of the humoral response in the host defense against Ehrlichia is supported by the observations showing that transfer of immune serum obtained from immunocompetent C57BL/6 mice as well as antibodies specific to the 28-kDa major outer membrane proteins of E. chaffeensis to C57BL/6 SCID mice provides significant, but transient, protection from disease. 6 Since infection of immunocompetent mice with E. chaffeensis does not result in severe disease, and infection of SCID mice results in fatal disease that does not mimic the histopathological findings in HME, we examined the immunopathological mechanisms of resistance and susceptibility to monocytotropic ehrlichiosis in immunocompetent mice employing other ehrlichial species that are phylogenetically related to E. chaffeensis.…”
Section: Introductionmentioning
confidence: 97%
“…The factors influencing disease susceptibility in humans have not been defined, although immunocompromised individuals appear to be particularly susceptible to serious disease (11). In previous studies, which used a mouse model for E. chaffeensis infection, it was demonstrated that susceptibility was correlated with immunodeficiency (12,13). Infected SCID mice developed severe and fatal disease that bore resemblance to human monocytic ehrlichiosis (12).…”
mentioning
confidence: 99%
“…In previous studies, which used a mouse model for E. chaffeensis infection, it was demonstrated that susceptibility was correlated with immunodeficiency (12,13). Infected SCID mice developed severe and fatal disease that bore resemblance to human monocytic ehrlichiosis (12). Studies of the immunological basis of disease resistance revealed that passive transfer of polyclonal Abs provided significant protection to the susceptible SCID mice (9).…”
mentioning
confidence: 99%